On the Persistence of Job Creation in Old and New Firms - René Böheim; Alfred Stiglbauer; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2008)
We suggest a new method to analyze the success of firm creation by looking at the persistence of new jobs created in old and in new firms. Compared to survival rates of new versus old firms, this measure has the advantage that the sustainability of job creation in different circumstances is investigated. We analyze 21 years of job creation in Austria and find that new jobs last significantly longer in new than in old firms. Moreover, the survival of new jobs depends upon the state of the business cycle at the time of job creation, on the number of jobs created, and, for existing firms, on firm age.
Keywords: J23; J63; E24; E32; 330; job creation; new firms; reallocation; persistence; Unternehmensgründung; Unternehmenserfolg; Konjunktur; Beschäftigungseffekt; Arbeitsplatz; Schätzung; Österreich